2018
DOI: 10.1002/adma.201802418
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctionality and Mechanical Actuation of 2D Materials for Skin‐Mimicking Capabilities

Abstract: Human skin serves as a multifunctional organ with remarkable properties, such as sensation, protection, regulation, and mechanical stretchability. The mimicry of skin's multifunctionalities via various nanomaterials has become an emerging topic. 2D materials have attracted much interest in the field of skin mimicry due to unique physiochemical properties. Herein, recent developments of using various 2D materials to mimic skin's sensing, protecting, and regulating capabilities are summarized. Next, to endow hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 78 publications
0
48
0
Order By: Relevance
“…The crumple-textured MXene electrode exhibited 30% higher resistances than the planar MXene one, since electrons were required to pass across the circuitous pathways of complex topographies. [34] The symmetric MXene electrodes were next immersed into 0.1 m BeSO 4 solution for 24 h followed by extensive water rinsing. A quasi-solid-state gel electrolyte composed of 1.0 m ZnSO 4 , 15.0 w/v% of gelatin, and 20 µL of 25 vol% glutaraldehyde was prepared and coated onto the symmetric Be 2+ -MXene electrodes to complete the fabrication of c-Be 2+ -MXene MSC.…”
Section: Microsupercapacitors With Crumple-textured Be 2+ -Mxene Elecmentioning
confidence: 99%
“…The crumple-textured MXene electrode exhibited 30% higher resistances than the planar MXene one, since electrons were required to pass across the circuitous pathways of complex topographies. [34] The symmetric MXene electrodes were next immersed into 0.1 m BeSO 4 solution for 24 h followed by extensive water rinsing. A quasi-solid-state gel electrolyte composed of 1.0 m ZnSO 4 , 15.0 w/v% of gelatin, and 20 µL of 25 vol% glutaraldehyde was prepared and coated onto the symmetric Be 2+ -MXene electrodes to complete the fabrication of c-Be 2+ -MXene MSC.…”
Section: Microsupercapacitors With Crumple-textured Be 2+ -Mxene Elecmentioning
confidence: 99%
“…Research on the fabrication of highly stable chemical sensors was reported, e.g., by use of passivation layers [242,243] and introducing cross-linking agents. [32,244] 1D and 2D materials were also widely used in increasing the sensitivity of (bio)chemical sensors, [245,246] such as introducing nanowires and nanotubes into the active layers to form the direct path for charge transport. [247][248][249] Pentacene/TSB3 [71] 6.3 Methanol vapor NA NA NA Nanoporous-structured semiconductor NDI3HU-DTYM2 [92] NA NH 3 NA 0.1 ppb NA Porous monolayer P3HT-azide [32] 0.32 Liquid analytes NA 1% methanol or ethanol NA (PEN) Container molecules Pentacene [34] 0.014 DNA 74 ng cm À2 650 ng ml À1 NA NA Graphene [205] NA DNA NA %1 fM NA ssDNA on Au electrodes Graphene:PDMS [204] NA DNA NA %1 nM NA Solution gated…”
Section: Performance Optimization Of (Bio)chemical F-fet Sensorsmentioning
confidence: 99%
“…First, Chang et al found it difficult to realize high mechanical durability and stretchability for most 2D materials such as MXenes, limiting the positions where devices can be worn on the human body to some extent. (5) Consequently, designers should consider an appropriate form of wearable devices to guarantee the function of MXene-based sensors. Li's group also reported that most physical sensors such as MXene-based sensors lack a selfpowered function and require an external energy system.…”
Section: Body Motion Detectionmentioning
confidence: 99%
“…(4) Chang et al summarized the merits of using 2D materials in direct contact with the skin for biosensing, such as high stretchability, high chemical resistance against a wide range of toxins, and easy bending and fabrication. (5) The MXenes, a new family of 2D transition metal carbides and nitrides, have attracted widespread attention because of their excellent mechanical properties, electrical conductivity, hydrophilicity, ultrathin nanosheet-like structure, and multifunctional surfaces, as well as their excellent ion intercalation performance for electrochemical sensing compared with other 2D nanomaterials. MXenes were discovered in 2011 by Gogotsi and coworkers.…”
Section: Introductionmentioning
confidence: 99%